PENTINGNYA PENDIDIKAN DIGITAL DALAM MENINGKATKAN KESADARAN DAN KETERAMPILAN ANAK DALAM MENGHINDARI CYBERCRIME - setiawan, Rahmat; Putri Anjani, Ajeng Galuh; Ade Putra, Bayu; Febrianti, Adhela; Cahyani, Puput; Nastifa, Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
AbstractThis research aims to examine the importance of digital education in raising students' awareness and skills in avoiding the increasing threat of crime in the digital era. Digital education here includes an understanding of digital security, ethical use of the internet, as well as technical skills in identifying and avoiding potential cyber dangers. This research was conducted at SMAN 9 Mataram, targeting students of class X1 as the main participants. The research method used a mixed approach, with data collection techniques through in-depth interviews, observations, questionnaires, and literature studies related to digital education and the problem of cybercrime in children. The results showed that digital education can significantly improve students' awareness and skills in recognising and avoiding cybercrime threats. In addition, support from schools, and the government in the implementation of digital education also plays an important role in creating a safe digital environment that supports student development. This research is expected to contribute to the development of a more structured and systematic digital education curriculum at the secondary education level.